Template-free growth of copper-doped hydroxyapatite nanowhiskers and their use as uric acid electrochemical sensor. (December 2022) - Chatterjee, Tuli; Chatterjee, Piyali; Chakraborty, Amit K.; Pradhan, Swapan Kumar; Meikap, Ajit Kumar
Abstract: We have synthesized copper-doped hydroxyapatite (Cu HAp) bioceramic nanowhiskers (aspect ratio ˃ 85) by a surfactant-free hydrothermal route. The detailed structural and compositional characterizations confirm the existence of catalytic multivalent Cu 1+ /Cu 2+ dopant ions and secondary β TCP phase. The dopant-induced oxygen vacancies promote active sites on the mesoporous surface (specific area ∼ 60.4 m 2 /g) for electrochemical applications. The electrochemical studies of the fabricated Cu HAp FTO revealed good response, sensitivity and stability towards uric acid (lowest stable detection limit ∼0.5 μM) in the lower and higher concentration regimes respectively. Thus, our fabricated Cu HAp shows surface-dependent electrochemical activities and non-enzymatic selective response to uric acid. Graphical Abstract: Novel nanowhisker shaped mesoporous copper-doped hydroxyapatite has been employed for catalytic activity and sensing. Three electrode-based non-enzymatic electrochemical sensing of uric acid has been studied by voltammetry and amperometry. Multivalent dopant-induced oxygen vacancies and presence of secondary phase regulates the active sites on the whisker surface. ga1 Highlights: Copper-doped hydroxyapatite synthesis by surfactant-free hydrothermal route. Novel mesoporous nanowhisker-shaped morphology of high specific surface area. Multivalent doping induced oxygen vacancies promote active sites on surface. Stable eco-friendly non-enzymatic electrochemical sensor of uric acid. Good sensitivity, selectivity, fast response and reproducibility is achieved.